The year 1917 [compact disc] : music in turbulent times. - Prohaska, Anna; Bostridge, Ian; Argerich, Martha, 1941-; Britten, Benjamin, 1913-1976; Cassard, Philippe; Drake, Julius, 1959-; Haas, Monique, 1909-1987; Pires, Maria João; Schneider, Eric (Pianist); Zimerman, Krystian; Dumay, Augustin; Mintz, Shlomo, 1957-; et al. (Deutsche Grammophon, 2017)
"1917 was a year of turbulence--both artistically and politically, it was the penultimate year of World War One, the year of the Russian Revolution and a year that demonstrates the artistic and cultural changes that happened across the world at the beginning of the 20th century. Discover 1917 through the music surrounding this pivotal year. Read fascinating notes by Michael Stegemann that explore the stories and the history behind the music. Listen to Stravinsky and Shostakovich, Debussy and Satie recorded by some of the greatest musicians past and present."--Container.